Chemokine networks modulating natural killer cell trafficking to solid tumors. (June 2021) - Yao, Xue; Matosevic, Sandro
Graphical abstract: Highlights: Chemokine receptors CCR2, CCR5, CCR7, CXCR3, and CX3CR1, in association with their ligands, drive the intratumoral trafficking of NK cells. Solid tumors alter chemokine receptor/ligand axes which in turn limit or impair the trafficking of NK cells. A number of therapeutic strategies aimed at augmenting chemokine receptor/ligand interactions with NK cells are being investigated. Abstract: Natural killer (NK) cell-based cell therapy has been emerging as a powerful weapon in the treatment of multiple malignancies. However, the inadequate infiltration of the therapeutic NK cells into solid tumors remains a big challenge to their clinical utility. Chemokine networks, which play essential roles in the migration of lymphocytes, have been recognized as critical in driving the intratumoral infiltration of NK cells via interactions between soluble chemokines and their receptors. Often, such interactions are complex and disease-specific. In the context of NK cells, chemokine receptors of note have included CCR2, CCR5, CCR7, CXCR3, and CX3CR1. The immunobiology of chemokine-receptor interactions has fueled the development of approaches that hope to improve the infiltration of NK cells into the microenvironment of solid tumors. Stimulation of NK cells ex vivo in the presence of various cytokines (such as IL-2, IL-15, and IL-21) and genetic engineering of NK cells have been utilized to alter the chemokine receptor profile and generate NK cells with higher infiltrating capacity. Additionally, the immune-suppressive tumor microenvironment has also been targeted, by introducing, either directly or indirectly, chemokine ligands which NK cells are able to respond to, ultimately creating a more hospitable niche for NK cell trafficking. Such strategies have promoted the infiltration and activity of infused NK cells into multiple solid tumors. In this review, we discuss how chemokine receptors and their ligands coordinate and how they can be manipulated to regulate the trafficking, distribution, and residence of NK cells in solid tumors.